PAI TEACHERS’ STRATEGIES IN IMPROVING THE QUALITY OF LEARNING DURING THE COVIDS 19 PANDEMIC - Ali Mansur (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2022)
The Covid-19 pandemic has significantly impacted various aspects of life, including the economy, social relations, industry, and especially education. School closures as a preventive measure against the spread of the virus forced the learning process to shift from face-to-face instruction to online, internet-based learning. In the early phase of the pandemic, the quality of instruction declined due to the lack of preparedness in terms of systems, strategies, and technological mastery among both teachers and students. The digitalization of learning required teachers to integrate social media and online platforms effectively as instructional tools. In this context, the implementation of appropriate learning strategies became crucial. Inquiry-based learning is relevant for fostering students’ critical, analytical, and creative thinking skills, while the Contextual Teaching and Learning (CTL) approach enables students to connect learning materials with real-life situations, helping them remain adaptive during crisis conditions. For Islamic Religious Education teachers, these challenges are even more complex, as they are responsible not only for students’ cognitive development but also for moral and character formation. Therefore, improving the quality of teaching and learning during the pandemic largely depends on teachers’ professional competence, particularly in applying innovative instructional strategies and utilizing digital media pedagogically.